THU0122 Etanercept Treatment Does Not Adversely Affect Traditional Cardiovascular Risk Factors in Patients with Rheumatoid Arthritis. (15th July 2016) - Deodhar, A.; Bitman, B.; Yang, Y.; Collier, D.
Abstract : Background: Patients with rheumatoid arthritis (RA) are at increased risk of cardiovascular (CV) disease. Objectives: To evaluate changes in metabolic and lipid CV risk factors in patients with RA treated with etanercept (ETN) Methods: This was an exploratory analysis in a randomized, double-blind, placebo-controlled study to evaluate the efficacy and safety of ETN in patients with moderate RA despite disease-modifying antirheumatic drug therapy. Adults with active, moderate RA (3.2 < DAS28-CRP ≤ 5.1) for ≥6 months and receiving a stable dose of methotrexate for ≥8 weeks were randomized 1:1 to receive ETN 50 mg or placebo (PBO) weekly for 12 weeks; after week 12, all patients received ETN 50 mg weekly for 12 weeks. Laboratory tests evaluated baseline, week-12, and week-24 levels of metabolic and lipid analytes, and shifts in grade (low, normal, or high). Results: In total, 210 patients enrolled: 104 PBO and 106 ETN; 77% female, 86% white, and mean (SD) age 56 (12) years. There were 14% with a medical history of type 2 diabetes and 30% a medical history of hyperlipidemia or hypercholesterolemia; 22% were receiving statins, 10% oral antidiabetic medications, 3% insulin, and 52% prednisone. Baseline, week-12, and week-24 values for each analyte are listed below. Over 24 weeks, there were no significant changes in metabolic or lipid analytes. Patients with diabetes and hyperlipidemia resembled the overall study population, except for decreases in fasting glucose and insulin through week 12 and slight decreases in hemoglobin A1C through week 24 in diabetics receiving ETN (n=17). For the majority of patients, all analytes were in the normal range at baseline and remained normal at week 24.There were no gross abnormalities in liver function tests. Safety results are consistent with the current safety profile. Conclusions: Treatment with ETN did not adversely affect the levels of traditional metabolic and lipid CV risk factors in patients with RA. Results in patients with diabetes are hypothesis generating and might be clinically relevant if demonstrated in a larger study. Disclosure of Interest: A. Deodhar Grant/research support from: AbbVie, Amgen Inc., Boehringer Ingelheim, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen Inc., Boehringer Ingelheim, Janssen, Novartis, Pfizer, and UCB, B. Bitman Shareholder of: Amgen Inc., Employee of: Amgen Inc., Y. Yang Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Collier Shareholder of: Amgen Inc., Employee of: Amgen Inc.